Implementasi Penanganan Surat Masuk dan Keluar Berbasis Digital Menggunakan Aplikasi E-Surat terhadap Efektivitas Administrasi di Dinas Lingkungan Hidup Kabupaten Gianyar - Ni Wayan Eva Lia Putri; Gede Pradiva Adiningrat; Putu Eka Suryadana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
This study aims to analyze the digital-based incoming and outgoing mail handling process using the E-Surat application and identify the obstacles encountered in its implementation on administrative effectiveness at the Environmental Agency of Gianyar Regency. The research employed a descriptive-analytical qualitative approach with six informants purposively selected from three management levels. Data were collected through observation, in-depth interviews, and documentation during August 2024. The findings revealed that the digital mail handling process has been conducted through a structured mechanism involving the Secretariat, Leadership, and Target Divisions, yielding positive impacts such as increased disposition speed, ease of archive retrieval, and archiving efficiency. However, the system's effectiveness remains suboptimal due to inaccurate tracking and notification features, hybrid print-sign-scan procedures, the absence of Digital Signature policy, the obligation to manage two parallel systems (E-Surat and Srikandi), server instability, and limited human resource competency. This study recommends strengthening digital signature policies, system integration, technological infrastructure enhancement, and sustainable human resource capacity development. Keywords: E-Surat, administrative effectiveness, incoming mail, outgoing mail, digitalization